Strengthening food security: a conceptual scholarly examination of the linkages between food loss and food waste / Aliffaizi Arsat ... [et al.] - Arsat, Aliffaizi; Zulkifly, Muhammad Izzat; Abdul Majid, Mohd Aliff; Mohd Zahari, Mohd Salehuddin (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
In this forthcoming qualitative research, a critical exploration of the vexing challenge of food loss and waste within the Malaysian context is undertaken. This inquiry engages with key stakeholders, including the Ministry of Agriculture and Food Security, alongside restaurant and foodservice providers. Utilizing in-depth interviews, the study unravels the underlying causes of food loss and waste, discerns the impact of government policies, scrutinizes the formidable challenges encountered by the foodservice industry, and spotlights sustainable practices as well as collaborative endeavours geared toward addressing this paramount issue. The envisioned findings are expected to unveil a multifaceted landscape of factors that contribute to food loss and waste. These encompass supply chain inefficiencies, intricate consumer behaviour patterns, and the formidable regulatory challenges that define this complex issue. The chosen research methodology, characterized by in-depth interviews, is aptly suited to unearth the nuanced struggles faced by restaurant and foodservice providers, offering valuable insights into the sustainable practices they employ to mitigate food waste and the cooperative initiatives fostering intersectoral collaboration. The significance of this impending study lies in its potential to craft policy recommendations and delineate strategies designed to bolster the reduction of food loss and waste. By shedding light on the intricate nature of this challenge and the evolving efforts undertaken to combat it, the research contributes to a future characterized by a more sustainable and conscientious food industry in Malaysia. The implications of this work extend to environmental conservation, economic efficiency, and the fortification of food security in the years to come.